How power affects people Activating, wanting, and goal seeking. [article]. - Guinote, Ana
Sociocognitive research has demonstrated that power affects how people feel, think, and act. In this article, I review literature from social psychology, neuroscience, management, and animal research and propose an integrated framework of power as an intensifier of goal-related approach motivation. A growing literature shows that power energizes thought, speech, and action and orients individuals toward salient goals linked to power roles, predispositions, tasks, and opportunities. Power magnifies self-expression linked to active parts of the self (the active self), enhancing confidence, self-regulation, and prioritization of efforts toward advancing focal goals. The effects of power on cognitive processes, goal preferences, performance, and corruption are discussed, and its potentially detrimental effects on social attention, perspective taking, and objectification of subordinates are examined. Several inconsistencies in the literature are explained by viewing power holders as more flexible and dynamic than is usually assumed. -- (from the author)